Presence of trace elements in sediment of Can Gio mangrove forest, Ho Chi Minh city, Vietnam - Hung, Tran Trong; Tu, Tran Anh; Huyen, Dang Thuong; Desmet, Marc (Vietnam Journal of Earth Sciences, 2019)
Can Gio mangrove forest (CGM) is located downstream of Ho Chi Minh City (HCMC), situated between an estuarine system of Dong Nai - Sai Gon river and a part of Vam Co river. The CGM is the largest restored mangrove forest in Vietnam and the UNESCO’s Mangrove Biosphere Reserve. The CGM has been gradually facing to numeric challenges of global climate change, environmental degradation and socio-economic development for the last decades. To evaluate sediment quality in the CGM, we collected 13 cores to analyze for sediment grain size, organic matter content, and trace element concentration of Cd, Cr, Cu, Ni, Pb, Zn. Results showed that trace element concentrations ranged from uncontaminated (Cd, Cu, and Zn) to very minor contaminated (Cr, Ni, and Pb). The concentrations were gradually influenced by suspended particle size and the mangrove plants.ReferencesAnh M.T., Chi D.H., Vinh N.N., Loan T.T., Triet L.M., Slootenb K.B.-V., Tarradellas J., 2003. Micropollutants in the sediment of Sai Gon – Dong Nai rivers: Situation and ecological risks. Chimia International Journal for Chemistry, 57, 09(0009–4293), 537–541.Baruddin N.A., Shazili N.A., Pradit S., 2017. Sequential extraction analysis of heavy metals in relation to bioaccumulation in mangroves, Rhizophora mucronata from Kelantan delta, Malaysia. AACL Bioflux, 10(2), 172-181. Retrieved from www.bioflux.com/aacl.Bravard J.-P., Goichot M., Tronchere H., 2014. An assessment of sediment transport processes in the lower Mekong river based on deposit grain size, the CM technique and flow energy data. Geomorphology, 207, 174-189.Cang L.T., Thanh N.C. 2008. Importing and exporting sediment to and from mangrove forest at Dong Trang estuary, Can Gio district, Ho Chi Minh city. Science & Technology Development, 11(04), 12-18.Carignan J., Hild P., Mevelle G., Morel J., Yeghicheyan D., 2001. Routine analyses of trace elements in geological samples using flow injection and low-pressure on-line liquid chromatography coupled to ICP-MS: A study of geochemical reference materials BR, DR-N, UB-N, AN-G and GH. The Journal of Geo standard and Geoanalysis, 187-198.Carlson P.R., Yarbro L.A., Zimmermann C.F., Montgomery J.R., 1983. Pore water chemistry of an overwash mangrove island. Academy Symposium: Future of the Indian River System, 46(3/4), 239-249. https://www.jstor.org/stable/24320336.Chatterjee M., Canário J., Sarkar S.K., Branco V., Godhantaraman N., Bhattacharya B.D., Bhattacharya A., 2012. Biogeochemistry of mercury and methylmercury in sediment cores from Sundarban mangrove wetland, India—a UNESCO World Heritage Site. Environ Monit Assess, 184, 5239–5254.Claudia R., Huy N.V., 2004. Water allocation policies for the Dong Nai river basin in Viet Nam: An integrated perspective. EPTD Discussion Paper, 127, 01-52.Folk R.L., Ward W.C., 1957. Brazos River bar: A study in the significance of grain size parameters. Journal of Sedimentary Petrology, 27(1), 3-26.Furukawaa K., Wolanski E., Mueller H., 1997. Currents and sediment transport in mangrove forests. Estuarine, Coastal and Shelf Science, 44, 301-310.Hai H.Q., Tuyen N.N., 2011. Coastal Erosion of Can Gio district Ho Chi Minh City due to the global climate change. The journal of development of technology and science, 14, 17-28.HCM SO S.O., 2015. Annual statistic data in 2015 for HCM city. Ho Chi Minh city: Statistic office of HCM city.HCMC, 2017. Decision No. 3901 on approving the areas of forest and land in HCM city in 2016. Ho Chi Minh: The people's committee of HCM city.Herut B., Sandler A., 2006. Normalization methods for pollutants in marine sediments: review and recommendations for the Mediterranean. Haifa 31080: Israel Oceanographic & Limnological Research: IOLR Report H18/2006.Hong P.N., San H.T., 1993. Mangroves of Vietnam: Chapter VI Human impacts on the mangrove ecosystem. Bangkok 10501: IUCN - The International Union for Conservation of Nature, ISBN: 2-8317-0166-x.Hubner R., Astin K.B., Herbert R.J., 2009. Comparison of sediment quality guidelines (SQGs) for the assessment of metal contamination in marine and estuarine environments. Journal of Environmental Monitoring, 11, 713–722.IAEA, 2003. Collection and preparation of bottom sediment samples for analysis of radionuclides and trace elements. Vienna, Austria: International Atomic Energy Agency, IAEA-TECDOC-1360, ISBN 92–0–109003–X.Jingchun L., Chongling Y., Ruifeng Z., Haoliang L., Guangqiu Q., 2008. Speciation changes of Cd in mangrove (Kandelia Candel L.) rhizosphere sediments. Bull Environ Contam Toxicol, 231-236. Doi:10.1007/s00128-007-9351-z.Kalaivanan R., Jayaprakash M., Nethaji S., Arya V., Giridharan L., 2017. Geochemistry of Core Sediments from Tropical Mangrove Region of Tamil Nadu: Implications on Trace Metals. Journal of Earth Science & Climatic Change, ISSN: 2157-7617., 8(1.1000385), 1-10. Doi:10.4172/2157-7617.1000385.Kathiresan K., Saravanakumar K., Mullai P., 2014. Bioaccumulation of trace elements by Avicennia marina. Journal of Coastal Life Medicine, 2(11), 888-894.Kitazawa T., Nakagawa T., Hashimoto T., Tateishi M., 2006. Stratigraphy and optically stimulated luminescence (OSL) dating of a Quaternary sequence along the Dong Nai River, southern Vietnam. Journal of Asian Earth Sciences, 27, 788–804.Lacerda L.D., 1998. Trace metals of biogeochemistry and diffuse pollution in mangrove (M. Vannucci, Ed.) Mangrove ecosystem occassional papers (ISSN: 0919-1348), 2, 1-72.Laura H., Probsta A., Probsta J.L., Ulrich E., 2003. Heavy metal distribution in some French forest soils: evidence for atmospheric contamination. The Science of Total Environment, 195-210.Li R., Li R., Chai M., Shen X., Xu H., Qiu G., 2015. Heavy metal contamination and ecological risk in Futian mangrove forest sediment in Shenzhen Bay, South China. Marine Pollution Bulletin, 101, 448–456.Long E., Morgan L.G., 1990. The potential for biological effects of sediment-sorted contaminants tested in the national status and trends program. Seattle, Washington: NOAA Technical Memorandum NOS OMA 52.Long E.R., Field L.J., MacDonald D.D., 1998. Predicting toxicity in marine sediments with numerical sediment quality guidelines. Environmental Toxicology and Chemistry, 17, 714–727. http://onlinelibrary.wiley.com/doi/10.1002/etc.5620170428/abstract;jsessionid=C5264A1AD0.7ACCA9B4EF9A088BE2EDE9.f04t04Long E.R., MacDonald D.D., Smith S.L., Calder F.D., 1995. Incidence of adverse biological effects within ranges of chemical concentration in marine and estuarine sediments. Environmental management, 19, 81-97.Maiti S.K., Chowdhury A., 2013. Effects of Anthropogenic Pollution on Mangrove Biodiversity: A Review. Journal of Environmental Protection, 4, 1428-1434.Marchand C., Allenbach M., Lallier-Verges E., 2011. Relation between heavy metal distribution and organic matter cycling in mangrove sediments (Conception Bay, New Caledonia). Geoderma, Elsevier, 160 (3-4), 444-456.Mohd F.N., Nor R.H., 2010. Heavy metal concentrations in an important mangrove species, Sonneratia caseolaris, in Peninsular Malaysia. Environment Asia, 3, 50-53.Muller G., 1979. Schwermetalle in den Sedimenten des Rheins - Veränderungen seit 1971. Umschau, 778-783.Nam V.N., 2007. Restoration of Can Gio mangrove forest: Its structure and function in comparison between the ecosytems of plantion and nature mangrove forest. Workshop on the thesis between Germany and Vietnam.Nickerson N.H., Thibodeau F.R., 1985. Association between pore water sulfide concentrations and the distribution of mangroves. Biogeochemistry, 1, 183-192.Ong Che R.G., 1999. Concentration of 7 Heavy Metals in Sediments and Mangrove Root Samples from Mai Po, Hong Kong. Marine Pollution Bulletin, 39, 269-279.Passega R., 1957. Texture as characteristics of clastic deposition. Publisher: American Association of Petroleum Geologists.Passega R., 1964. Grain size representation by CM patterns as a geological tool. J Sediment Petrol, 34, 830–847.Phuoc V.L., An D.T., Cang L.T., Chung B.N., Tien N.V., 2010. Study the sediment dynamics in Can Gio mangrove forest (Nang Hai site, Ho Chi Minh city). Ho Chi Minh city: The final report of National University Ho Chi Minh city, No. B2009-18-36.Pumijumnong N., Danpradit S., 2016. Heavy metal accumulation in sediments and mangrove forest stems from Surat Thani province, Thailand. The Malaysian forester, 79(1&2), 212-228.QCVN43:2012/BTNMT, 2012. QCVN43:2012/BTNMT: National technical regulation on the sediment quality, Ha Noi: Ministry of natural resources and environment of Vietnam.Qiao S., Shi X., Fang X., Liu S., Kornkanitnan N., Gao J., Yu Y., 2015. Heavy metal and clay mineral analyses in the sediments of Upper Gulf of Thailand and their implications on sedimentary provenance and dispersion pattern. Journal of Asian Earth Sciences, 114, 488–496.Rollinson H. R., 1993. Using geochemical data for evaluation, presentation and interpretation. UK: Longman Group UK Limited ISBN-0-582-06701-4.Spalding M., Blasco F., Field C., 2010. World atlas of mangrove. Cambridge: Earthscan in UK and US, ISBN: 978-1-84407-657-4.Strady E., Dang V.B., Némery J., Guédron S., Dinh Q.T., Denis H., Nguyen P.D., 2016. Baseline seasonal investigation of nutrients and trace metals in surface waters and sediments along the Saigon River basin impacted by the megacity of HCM, Viet Nam. Environ Sci Pollut Res, 1-18. doi:10.1007/s11356-016-7660-7.Tam N.F., Wong Y.S., 1996. Retention and distribution of heavy metals in mangrove soils receiving wastewater. Environment pollution, 94(5), 283-291.Thomas N., Lucas R., Bunting P., Hardy A., Rosenqvist A., Simard M., 2017. Distribution and drivers of global mangrove forest change, 1996– 2010. PLoS ONE, 12(6): e0179302, 1-14. Doi:10.1371/journal.pone.0179302.Thuy H.T., Loan T.T., Vy N.N., 2007. Study on environmental geochemistry of heavy metals in urban canal sediments of Ho Chi Minh city. Science and Technology Development, 10(01), 1-9.Toan T.T., Bay N.T., 2006. A study on the tendency of accretion and erosion in Can Gio coastal zone. Vietnam-Japan estuary workshop, 184-194.Tri N.H., Hong P.N., Cuc L.T., 2000. Can Gio Mangrove Biosphere Reserve Ho Chi Minh city, Ha Noi, Viet Nam. Ha Noi: Hanoi University Publisher.Truong T.V., 2007. Planning for water source of Dong Nai river basin. Retrieved from Water Resources Planning: http://siwrp.org.vn/tin-tuc/quy-hoach-tai-nguyen-nuoc-luu-vuc-song-dong-nai_143.html.Tuan L.D., Oanh T.T., Thanh C.V., Quy N.D., 2002. Can Gio mangrove biosphere reserve. HCM city, Vietnam: Agriculture Publisher.Tue N.T., Quy T.D., Amono A., 2012. Historical profiles of trace element concentrations in Mangrove sediments from the Ba Lat estuary, Red river, Vietnam. Water, Air & Soil Pollution, ISSN 0049-6979, 223(3), 1315-1330.Twilley R., Chen R., Hargis T., 1992. Carbon sinks in mangroves and their implications to carbon budget of tropical coastal ecosystems. Water, Air & Soil pollution, Netherland, 64, 265-288.UN Environment Program, 2006. Methods for sediment sampling and analysis. Palermo (Sicily), Italy: United Nation Environment Program.UNESCO, 2000. List of Biosphere reserves approved by MAB committee belonging to UNESCO. Retrieved from United Nations, Educational, Scientific, Cultural Organization (UNESCO): http://www.unesco.org/new/en/natural-sciences/environment/ecological-sciences/biosphere-reserves/asia-and-the-pacific.Vandenberghe N., 1975. An evaluation of CM patterns for grain size studies of fine grained sediments. Sedimentology, 22, 615-622.Vinh B.T., Ichiro D., 2012. Erosion mechanism of cohesive river bank and bed of Soai Rap river (Ho Chi Minh city). J. Sci. of the Earth, 34(2), 153-161.Wang J., Du H., Xu Y., Chen K., Liang J., Ke H., Cai M., 2016. Environmental and Ecological Risk Assessment of Trace Metal Contamination in Mangrove Ecosystems. BioMed Research International, Article ID 2167053, 1-14. Doi:10.1155/2016/2167053.Wedepohl K.H., 1995. The composition of the continental crust. Geochimica et Cosmochimica Acta, 59(7), 1217-1232.Woodroffe C., Rogers K., McKee K., Lovelock C., Mendelssohn I., Saintilan N., 2016. Mangrove sedimentation and response to relative sea level rise. The Annual Review of Marine Science, 8, 243-266.Zhang J., Liu C.L., 2002. Riverine Composition and Estuarine Geochemistry of Particulate Metals in China-Weathering Features, Anthropogenic Impact and Chemical Fluxes. Estuarine, Coastal and Shelf Science, 54(6), 1051-1070.Zhang W., Feng H., Chang J., Qu J., Xie H., Yu L., 2009. Heavy metal contamination in surface sediments of Yangtze River intertidal zone: An assessment from different indexes. Environmental Pollution, 157, 1533-1543.Zheng W.-j., Xiao-yong C., Peng L., 1997. Accumulation and biological cycling of heavy metal elements in Rhizophora stylosa mangroves in Yingluo Bay, China. Marine ecology progress series, 159, 293-301.